Contribuição dos naturalistas do Século XIX para o conhecimento da ictiofauna de água doce no Brasil - Oliveira, Mariana Bispo (2023)
Objective: To evaluate the contribution of five naturalists (Johann Natterer, Johan Baptist Spix, Louis Agassiz, Jacob Heckel, Rudolf Kner and Francis de Castelnau) to the knowledge of the taxonomic diversity of the freshwater ichthyofauna in Brazil between the years 1829 and 1859. Methods: Two data matrices were constructed: one with information on freshwater fish in Brazil known up to 2021 and the other based on the list of fish species in South America presented by Castelnau (1855). Both were complemented with information on taxonomy, geographic distribution, authorship and geographic distribution. From the first, the Taxonomic Diversity Index (Δ) was calculated to evaluate the contribution of naturalists in order to demonstrate the importance of Castelnau in this group. Species richness was also determined, by hydrographic basin, based on the species described by the considered naturalists. Results: The ichthyofauna species identified by the five naturalists totaled 171. Castelnau was the naturalist with the greatest contribution to knowledge of the taxonomic diversity (Δ= 87.69) of the Brazilian ichthyofauna, followed by Agassiz (Δ=85.45) and Spix & Agassiz (85.44). Conclusion: The considered naturalists presented endemic species with high ecological and economic value. The Amazon basin had the highest number of species and Castelnau had the highest rate of taxonomic diversity among those considered.